The Online Fruit and Vegetable Purchase Decisions: The Roles of Lifestyle, Promotion, and Service Quality - Sukardiman, Diah Fistiani; Santo , Vianty Adelli; Kasmo, Arief Bowo Prayoga (AMAR (Andalas Management Review), 2025)
The transformation of modern lifestyles and technological advancements has driven a significant increase in the online purchase of fresh products, such as fruits and vegetables. This study aims to analyze the influence of lifestyle, promotion, and service quality on consumers’ purchasing decisions on the GoFruit.id platform. The population in this research comprises consumers who have made purchases on GoFruit.id, although the total population size is unknown. A sample of 100 respondents was obtained using purposive sampling and determined using the Rao formula (2006). Data were collected through a survey using structured questionnaires and analyzed using the Partial Least Squares (PLS) method. The results indicate that lifestyle has a positive and significant influence on purchase decisions. Similarly, service quality also shows a positive and significant effect. However, promotion does not have a significant effect on consumers' purchasing decisions. These findings suggest that online fruit and vegetable retailers should prioritize improving service quality and aligning products with consumer lifestyles rather than relying heavily on promotional strategies. Keywords: lifestyle, promotion, service quality, purchase decision, online shopping